Pharmacognostic Evaluation and Antioxidant Profiling of Five Varieties of Ribes nigrum Grown in Romania - Ruxandra Ștefănescu; Francisc Boda; Monica Sebestyen; Ioana Râșteiu; Eszter Laczkó-Zöld; Lénárd Farczádi (Plants)
Blackcurrants (Ribes nigrum L.) are recognized for their rich anthocyanin content, contributing to their health-promoting properties. This study explored the phytochemical profiles and antioxidant activities of five blackcurrant varieties (Gofert, Tiben, Ceres, Ronix, and Ruben) cultivated in Mureș County, Romania. Using HPLC-DAD analysis, cyanidin-rutinoside was identified as the predominant anthocyanin in all varieties. Ruben stood out with the highest anthocyanin concentration and antioxidant activity, highlighting its potential for functional food and nutraceutical applications. The high anthocyanin content determined in these varieties suggests the influence of hybridization and unique regional growing conditions. Antioxidant activity, assessed through 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) (ABTS) assays, showed strong correlations with anthocyanin content, though polyphenolic levels did not consistently align with antioxidant efficacy. These findings emphasize the importance of tailoring blackcurrant cultivation to optimize bioactive compound production and support further exploration of their therapeutic potential.